Two-Year College Distance-Learning Students With Psychological Disorders: Counseling Needs and Responses. Issue 4 (2nd October 2018) - Warren, Gretchen; Schwitzer, Alan M.
ABSTRACT: This article briefly reports on the needs of students with diagnosed psychological disorders who are enrolled in 2-year colleges and studying at a distance. A six-feature descriptive model was constructed that included three areas of need (Hurdle of Self-Disclosure, Hurdle of Personal Connection, Hurdle of Time Management) and three corresponding roles for counselors (Psycho-emotional Support, Relationship Support, Learning Support). We discuss the relationship between the descriptive model derived from the current study and the Universal Design for Learning (UDL) framework, which historically has been applied to work with this population. Implications for the roles of college psychotherapists at 2-year institutions are presented.